Dissociated profiles of sleep timing and sleep quality changes across the first and second wave of the COVID-19 pandemic. (November 2021) - Conte, Francesca; Cellini, Nicola; De Rosa, Oreste; Rescott, Marissa Lynn; Malloggi, Serena; Giganti, Fiorenza; Ficca, Gianluca
Abstract: Previous work showed a significant impact of the COVID-19 pandemic on Italians' sleep both during the first wave, when a total lockdown (TL) was imposed, and during the second wave, when a partial lockdown (PL) was mandated (autumn 2020). Here we complement these data by describing the profile of sleep across four time-points: the first and second lockdown (TL, PL) and the months preceding them (pre-TL, pre-PL). An online survey was completed by 214 participants (Mage = 36.78 ± 14.2 y; 159 F) during TL and again during PL. All sleep-related questions (including items of the Pittsburgh Sleep Quality Index) required a double answer, one referred to the current lockdown and one to the month preceding the lockdown. Bedtime and rise time were delayed in TL and then advanced in pre-PL and PL. Similarly, time in bed increased in TL and then decreased in pre-PL and PL. Sleep quality worsened in the two lockdowns compared to the preceding periods and the proportion of poor sleepers correspondingly increased in both lockdowns. Sleep habits and quality displayed different profiles across phases of the pandemic. Sleep timing was altered during the first lockdown and then returned towards baseline (likely due to normalized working schedules). Instead, sleep quality, which markedly worsened during both lockdowns, appears particularly sensitive to changes in life habits and psychological factors, independently of sleep habits. Our findings also point to a possible role of acute and chronic stress (experienced during the first and second wave, respectively) in modulating sleep changes across the pandemic waves. Highlights: Distinct sleep features evolved differently across 4 phases of the Covid-19 pandemic. Sleep timing appears affected by constraints of daily routines during the pandemic. Sleep quality reflects changes in psychological factors across the pandemic waves. Sleep changes across the waves may reflect a shift from acute to chronic stress.